2013
DOI: 10.1155/2013/274570
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 2‐Hydroxy‐3‐[(2‐aryloxyethyl)amino]propyl 4‐[(Alkoxycarbonyl)amino]benzoates

Abstract: A series of twenty substituted 2-hydroxy-3-[(2-aryloxyethyl)amino]propyl 4-[(alkoxycarbonyl)amino]benzoates were prepared and characterized. As similar compounds have been described as potential antimycobacterials, primary in vitro screening of the synthesized carbamates was also performed against two mycobacterial species. 2-Hydroxy-3-[2-(2,6-dimethoxyphenoxy)ethylamino]-propyl 4-(butoxycarbonylamino)benzoate hydrochloride, 2-hydroxy-3-[2-(4-methoxyphenoxy)ethylamino]-propyl 4-(butoxycarbonylamino)benzoate hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Epoxides 7a–9a and 13a (see below) were prepared from 4-aminobenzoic acid through reaction with methyl, ethyl, propyl and butyl chloroformiates giving appropriate 4-[(alkoxycarbonyl) amino]benzoic acids. Chlorides of these acids formed by thionyl chloride treatment gave desired epoxides 7a–9a and 13a after reaction with 2,3-epoxypropan-1-ol [53]. In the last step final compounds 7–9 were prepared by a reaction of the epoxides with 1-(4-phenyl)piperazine and then converted to the hydrochloride salts using ethereal HCl to enhance their solubility in water [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epoxides 7a–9a and 13a (see below) were prepared from 4-aminobenzoic acid through reaction with methyl, ethyl, propyl and butyl chloroformiates giving appropriate 4-[(alkoxycarbonyl) amino]benzoic acids. Chlorides of these acids formed by thionyl chloride treatment gave desired epoxides 7a–9a and 13a after reaction with 2,3-epoxypropan-1-ol [53]. In the last step final compounds 7–9 were prepared by a reaction of the epoxides with 1-(4-phenyl)piperazine and then converted to the hydrochloride salts using ethereal HCl to enhance their solubility in water [55].…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 2-hydroxy-3-[2-(4-methoxyphenoxy)ethylamino] propyl 4-(propoxycarbonylamino)benzoate hydrochloride ( 13 ) was described in Tengler et al [53]. The first main intermediate, oxiran-2-ylmethyl 4-[(propoxycarbonyl)amino]benzoate ( 13a ) was synthesized according to Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For individual substituents in the aniline part of the discussed compounds also electronic Hammett's σ parameters were predicted using the same software; they ranged from -0.29 to -0.27 for ortho-and parasubstituted compounds and from 0.10 to 0.14 for meta-substituted compounds. Experience has shown that a parameter representing the volume of the substituents on each compound relative to other members of the same series may often be correlated with biological measurement [23][24][25], therefore molar volume MV [cm -3 ] was also calculated. The predicted molecular descriptors of the studied compounds are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…22 Taking into account our previous experience in selenocyanate and diselenide chemistry [23][24][25] and the fact that we have recently reported some carbamates as potential antiproliferative drugs, 26 we decided to further extend our research by synthesising thirty new hybrid compounds in which selenocyanate or diselenide and carbamate moieties were combined. In these compounds the carbamate function, a group commonly found in antitumour active http compounds [27][28][29][30][31][32] acts as a link between the central and ending scaffolds, thus enabling their chemical accessibility and increasing polarity in this area as compared to our previously described structures. 23,[33][34][35] Besides, this group might facilitate the hydrolysis of the compounds towards anionic species that could act as prodrugs (Fig.…”
Section: Introductionmentioning
confidence: 99%